The influence of sex steroid hormones on the response to trauma and burn injury. Issue 1 (14th September 2017) - Al-Tarrah, K; Moiemen, N; Lord, JM
Abstract : Abstract: Trauma and related sequelae result in disturbance of homeostatic mechanisms frequently leading to cellular dysfunction and ultimately organ and system failure. Regardless of the type and severity of injury, gender dimorphism in outcomes following trauma have been reported, with females having lower mortality than males, suggesting that sex steroid hormones (SSH) play an important role in the response of body systems to trauma. In addition, several clinical and experimental studies have demonstrated the effects of SSH on the clinical course and outcomes following injury. Animal studies have reported the ability of SSH to modulate immune, inflammatory, metabolic and organ responses following traumatic injury. This indicates that homeostatic mechanisms, via direct and indirect pathways, can be maintained by SSH at local and systemic levels and hence result in more favourable prognosis. Here, we discuss the role and mechanisms by which SSH modulates the response of the body to injury by maintaining various processes and organ functions. Such properties of sex hormones represent potential novel therapeutic strategies and further our understanding of current therapies used following injury such as oxandrolone in burn-injured patients.